2004
DOI: 10.1534/genetics.104.031153
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Power of Statistical Methods for Detecting Adaptive Evolution in Protein Coding Sequences and for Identifying Positively Selected Sites

Abstract: The parsimony method of Suzuki and Gojobori (1999) and the maximum likelihood method developed from the work of Nielsen and Yang (1998) are two widely used methods for detecting positive selection in homologous protein coding sequences. Both methods consider an excess of nonsynonymous (replacement) substitutions as evidence for positive selection. Previously published simulation studies comparing the performance of the two methods show contradictory results. Here we conduct a more thorough simulation study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
514
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(522 citation statements)
references
References 37 publications
7
514
1
Order By: Relevance
“…Recently, alternative approaches based on maximum-likelihood models have been suggested that potentially provide more accurate estimates of d N /d S ratios and allow the identification of species-specific PSS (Yang and Bielawski, 2000;. In simulations, Wong et al (2004) demonstrated that the maximum-likelihood method has a good power and accuracy in detecting positive selection. It is particularly appropriate for detecting selection in MHC genes, where positive selection could be acting simultaneously in groups of codons (Suzuki and Nei, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alternative approaches based on maximum-likelihood models have been suggested that potentially provide more accurate estimates of d N /d S ratios and allow the identification of species-specific PSS (Yang and Bielawski, 2000;. In simulations, Wong et al (2004) demonstrated that the maximum-likelihood method has a good power and accuracy in detecting positive selection. It is particularly appropriate for detecting selection in MHC genes, where positive selection could be acting simultaneously in groups of codons (Suzuki and Nei, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For the serine peptidase family and each CRN subfamily, we firstly used the site-specific models [22,45,46] to identify positively selected codon sites in Bd and in oomycetes or bacteria, respectively. In this analysis, we compared models M1a vs .…”
Section: Methodsmentioning
confidence: 99%
“…Models are compared by a log-likelihood ratio test, LRT (LRT ¼ À2 times the difference in log-likelihood tested against a w 2 -distribution with the number of degrees of freedom equal to the number of additional random effects). It should be noted that the use of two degrees of freedom for the M8 vs M7 comparisons and one degree of freedom for the M8a vs M8 comparisons is considered conservative (Swanson et al, 2003;Wong et al, 2004).…”
Section: Sequence Analysismentioning
confidence: 99%